Ethics for journalists - Duncan, Sallyanne (Media skills, 2023)
"Ethics for Journalists critically explores many of the dilemmas that journalists face in their work and supports journalists in good ethical decision-making. From building trust, to combatting disinformation, to minimizing harm to vulnerable people through responsible suicide reporting, this book provides substantial analysis of key contemporary ethical debates and offers guidance on how to address them. Revised and updated throughout, this third edition covers: the influence of press freedom and misinformation on trust; the novel ethical challenges presented by social media; the need for diversity of sources and in the newsroom, specifically relating to gender, ethnicity, sexual orientation and disability; issues around vulnerable people-reporting traumatic events, bereaved people, suicide and privacy; health journalism and reporting a pandemic; the impact of regulation on professional standards. Taking an accessible and engaging approach, including expert reflections on personal and professional experience, Ethics for Journalists provides a wealth of insight for those in journalism, from students and trainees to specialist correspondents and experienced editors"--